Identifying the activity of nanocatalyst sites - Lee, Woong Hee (NATURE PUBLISHING GROUP, 2024)
There is no doubt that identifying active sites at the atomic scale for designing optimal catalysts is a great challenge. Now, by combining computational and experimental results, an advanced methodology is proposed for understanding the structure-activity relationship at the atomic level.